Quality of Louis melons stored under four storage temperatures - Morgado, Cristiane Maria Ascari; Mattiuz, Claudia Fabrino Machado; Muniz, Ana Carolina [UNESP]|Charles, Florence; Mattiuz, Ben-hur [UNESP] (Universidade Federal de Santa Maria, 2015)
This research aimed to establish the best temperature for the conservation of ‘Louis‘ melons. Fruit were stored under ambient condition (22°C and 80% RH) and under refrigeration (3°C - 80% RH, 6°C - 90% RH e 9°C - 80% RH) and evaluated for color and resistance of pulp, soluble solids, titratable acidity content, peroxidase, polyphenol oxidase, polygalacturonase and pectin methyl esterase activity and weight loss. ‘Louis‘ melons at 22°C showed greater reduction in soluble solids and titratable acidity content, and had higher activity of the enzyme polygalacturonase, culminating in conservation for 18 days. Melons stored at 6°C preserved the shelf-life for 25 days, showed the highest soluble solids and lower activity of peroxidase and polygalacturonase

Este trabalho teve como objetivo estabelecer a melhor temperatura para a conservação de melões ‘Louis‘. Os frutos foram armazenados sob condição de ambiente (22±2°C e 80±5% UR), sob refrigeração (3±1°C e 80±5% UR; 6±1°C e 80±5% UR; e 9±1°C e 80±5% UR) e avaliados quanto à coloração e firmeza da polpa, teores de sólidos solúveis, acidez titulável, atividade das enzimas peroxidase, polifenoloxidase, poligalacturonase e pectinametilesterase e perda de massa fresca. Os melões ‘Louis‘ armazenados a 22°C apresentaram maior redução nos teores de sólidos solúveis e acidez titulável, além de apresentarem maior atividade da enzima poligalacturonase, com conservação por até 18 dias. Os frutos armazenados a 6°C mantiveram a qualidade comercial durante 25 dias de armazenamento, apresentando os maiores teores de sólidos solúveis e menor atividade das enzimas peroxidase e poligalacturonase
Qualidade de melões Louis armazenados em quatro temperaturas
Keywords: Refrigeration storage; Shelf-life; Cucumis melo L; Armazenamento refrigerado; Vida de prateleira; Cucumis melo L